2018
DOI: 10.3390/polym10080833
|View full text |Cite
|
Sign up to set email alerts
|

Reactions with Wood Carbohydrates and Lignin of Citric Acid as a Bond Promoter of Wood Veneer Panels

Abstract: The reaction of citric acid with wood veneers was studied by Cross Polarization Magic Angle Spinning Nuclear Magnetic Resonance (CP MAS 13C NMR) and matrix assisted laser desorption ionization time of flight (MALDI ToF) mass spectrometry. The analysis showed that reactions of citric acid occurred with both lignin and carbohydrate constituents of wood. The reactions occurring are esterifications between the carboxylic acid functions of citric acid and the numerous aromatic and aliphatic hydroxyl groups of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 11 publications
3
42
0
3
Order By: Relevance
“…Another new peak located at around 1025 cm -1 was identified as the ether linkage C–O–R [42], which possibly formed by the dehydration condensation of furan compounds. In addition, several studies reported that citric acid could react with the hydroxyl group of wood components, which contributed to the bond strength [14,43]. Our results also corroborate this phenomenon (Figure 1).…”
Section: Resultssupporting
confidence: 89%
“…Another new peak located at around 1025 cm -1 was identified as the ether linkage C–O–R [42], which possibly formed by the dehydration condensation of furan compounds. In addition, several studies reported that citric acid could react with the hydroxyl group of wood components, which contributed to the bond strength [14,43]. Our results also corroborate this phenomenon (Figure 1).…”
Section: Resultssupporting
confidence: 89%
“…Umemura et al [ 57 ] suggested the reaction between carboxyl groups of CA and hydroxyl groups of wood constituents formed ester linkages that resulted in adhesivity and good bonding properties. The hypothesis has been proven by Del Menezzi et al [ 58 ] in a latter study. By using CP MAS 13 C NMR spectra, the reaction of wood with CA at 60 °C and 180 °C was investigated by Del Menezzi et al [ 58 ].…”
Section: Citric Acid As Main Bonding Component For Wood Compositessupporting
confidence: 65%
“…The hypothesis has been proven by Del Menezzi et al [ 58 ] in a latter study. By using CP MAS 13 C NMR spectra, the reaction of wood with CA at 60 °C and 180 °C was investigated by Del Menezzi et al [ 58 ]. Phenolic hydroxyl groups of guaiacyl type lignin were found to react with CA.…”
Section: Citric Acid As Main Bonding Component For Wood Compositessupporting
confidence: 65%
See 1 more Smart Citation
“…The pyrolysis products of citric acid (citraconic acid anhydride and itaconic anhydride) were also detected in the insoluble mass which suggested that citric acid participated in the curing reaction. It is worth noting that levoglucosenone (marked with XI), which is usually formed by heating glucose or oligosaccharide, was also observed in the insoluble mass; this indicated the saccharide possibly participated in the curing reaction [38]. Based on the results of the Py-GC/MS above, a possible chemical structure of part of the cured SC adhesive is shown in Figure 9.…”
Section: Py-gc/msmentioning
confidence: 93%